Vitamin A pretreatment protects NO-induced bovine mammary epithelial cells from oxidative stress by modulating Nrf2 and NF-κB signaling pathways. (13th April 2018) - Shi, H Y; Yan, S M; Guo, Y M; Zhang, B Q; Guo, X Y; Shi, B L
Abstract: It is known that physiological overproduction of nitric oxide (NO ) contributes to oxidative stress and inflammation. Our published studies indicated that vitamin A (VA ) reduces NO-induced oxidative stress in bovine mammary epithelial cells (BMECs ) by increasing antioxidant enzyme activities. However, the precise mechanism is unclear. The present study was conducted to examine the protective effects of VA on NO-induced damage to BMECs in vitro using diethylenetriamine nitric oxide (DETA-NO ) as the NO donor and to explore the intracellular signaling mechanisms of VA that involve nuclear factor erythroid 2-related factor (Nrf2 ) and nuclear factor kappa-B (NF-κB ). Subconfluent BMECs were divided into 10 treatment groups with 6 replicates per treatment and were cultured with dimethyl sulfoxide (DMSO, vehicle negative control) or 0, 0.05, 0.1, 0.2, 0.5, 1, 2, 3, or 4 μg/mL of VA for 24 h and then incubated in the absence or presence of DETA-NO (1, 000 μmol/liter) and VA for an additional 6 h. The results showed that exposure to DETA alone decreased cell proliferation compared with the negative control. Pretreatment with VA promoted the proliferation of BMECs, increased the activities of antioxidative enzymes including selenoprotein glutathione peroxidase (GPx ) and thioredoxin reductase (TrxR ) and their gene and protein expression but decreased NO and interleukin 1 (IL-1 ) contents in a quadratic manner ( P < 0.05). In addition, the expression of mRNA and protein of factors that are related to NF-κB or Nrf2 signaling pathways in BMECs were regulated by VA in a quadratic dose-dependent manner; VA at a concentration of 1 μg/mL exhibited the strongest effect. Together, these results suggest that VA promotes antioxidant functions of BMECs by regulating the synthesis of selenoproteins including GPx and TrxR and by reducing concentrations of IL-1 and NO in vitro by modulating Nrf2 and NF-κB signaling pathways.